2014
DOI: 10.1136/gutjnl-2014-308211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and virological predictors of hepatic flares in pregnant women with chronic hepatitis B

Abstract: 25% of women with chronic hepatitis B will demonstrate increased liver inflammation in the postpartum period. This is usually asymptomatic and resolves spontaneously. This is more likely if the woman is HBeAg-positive at baseline (2.56 times the risk), although flares also commonly occur in HBeAg-negative women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
3
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 19 publications
4
104
3
6
Order By: Relevance
“…However, restoration of the CMI function occurs during the postpartum period, and studies have reported higher than expected HBeAg seroconversion rates [24] and higher than normal rates of alanine aminotransferase (ALT) during the initial postpartum period in HBVinfected women [23,[25][26][27][28][29]. While most hepatic flares have been mild and resolved spontaneously [25], a small number of case reports indicate severe hepatitis flares leading to hepatic decompensation during the peripartum period [29].…”
Section: Effects Of Pregnancy On Hbv-associated Liver Diseasementioning
confidence: 95%
“…However, restoration of the CMI function occurs during the postpartum period, and studies have reported higher than expected HBeAg seroconversion rates [24] and higher than normal rates of alanine aminotransferase (ALT) during the initial postpartum period in HBVinfected women [23,[25][26][27][28][29]. While most hepatic flares have been mild and resolved spontaneously [25], a small number of case reports indicate severe hepatitis flares leading to hepatic decompensation during the peripartum period [29].…”
Section: Effects Of Pregnancy On Hbv-associated Liver Diseasementioning
confidence: 95%
“…A minority of patients required antiviral therapy for treatment of flare. Similarly, another observational study of 126 women with HBV followed through pregnancy found that 25 % of women had a postpartum flare, defined as two times the upper limit of normal ALT [47]. Most of the women included in this analysis were not taking antiviral medications during pregnancy.…”
Section: Postpartum Carementioning
confidence: 96%
“…Il tema della profilassi antibiotica in questa situazione è molto [ o n l y dibattuto e la letteratura specifica è piuttosto carente, per cui le raccomandazioni fatte sono basate prevalentemente sul parere di esperti. C'è chi non la ritiene necessaria, almeno nei difetti interatriali, 59 chi la ritiene ragionevole nelle pazienti ad alto rischio (precedente endocardite infettiva, difetti residui dopo la correzione chirurgica; nei primi sei mesi dopo la correzione chirurgica) 60 e chi la consiglia anche in situazioni di rischio non eccessivamente elevato. 61 Un altro aspetto non particolarmente chiaro riguarda il momento della pratica della profilassi, se va fatta in coincidenza con il parto (vaginale o cesareo) o meno.…”
Section: Messaggi Chiaveunclassified
“…Esacerbazioni lievi della malattia possono verificarsi dopo il parto. 58,59 Nella pratica clinica, le donne portatrici HBV-DNA positive devono essere informate per quanto riguarda la gravidanza, sia se sono in trattamento che se non lo sono. In tutti i casi, l'indicazione al trattamento, secondo le raccomandazioni attuali, dovrebbe essere considerato e discusso con la paziente.…”
Section: Epatite Virale Cronicaunclassified